Reactivity of Alkyldibenzothiophenes Using Theoretical Descriptors - Jose Luis Rivera; Pedro Navarro-Santos; Luis Hernandez-Gonzalez; Roberto Guerra-Gonzalez (Journal of Chemistry)
Theoretical calculations of the reactivity of dibenzothiophene and its methyl, dimethyl, and trimethyl derivatives show that local reactivity descriptors reproduce their experimental desulfurization reactivity trend if the first desulfurization step involves directly the sulfur atom, which only occurs if the sulfur atom is blocked at most by one methyl group. In the series of molecules {4,7-dimethyldibenzothiophene, x,4,7-trimethyldibenzothiophene (x=1,2,3)}, the most reactive molecule is 2,4,7-trimethyldibenzothiophene, and local descriptors show that the reactivity is linked to the activity of the sulfur atom, which is higher in 2,4,7-trimethyldibenzothiophene due to the position of the third methyl substitute, located in the para position with respect to the carbon bonded to the sulfur atom. The electrostatic potential of 2,4,7-trimethyldibenzothiophene shows one effective adsorption site, while 1,4,7-trimethyldibenzothiophene and 3,4,7-trimethyldibenzothiophene have more sites, contributing to the higher reactivity of 2,4,7-trimethyldibenzothiophene. The index of reactivity of other descriptors was evaluated and the effect of the position of the methyl substituents on adsorption parameters, as the dipole moment and the atomic charges were also studied.